Phytoremediation Efficiency of Some Evergreen Plant Genera for Lead Polluted Soil - Shilan Farhad Mamand; Nashmeel Saeed Khudhur; Dalshad Azeez Darwesh (Zanco Journal of Pure and Applied Sciences, 2020)
A pot experiment was performed to determine the efficiency of phytoremediation of some evergreen plants to lead in a polluted soil. The experiment was a factorial completely randomized design with three replications. The first factor was four evergreen plant genera involved Dodonaea viscosa L., Myrtus communis L., Platycladus orientalis L. and Ficus benjamina L. used as phytoremediators. Whereas, the second factor was different concentrations of lead (0, 100, 200 and 300 mg.kg-1) which were prepared using laboratory grade PbCl2. The results indicated that the highest bioaccumulation factor (BF) (39.15 and 19.39) were observed in Dodonaea viscosa and Ficus benjamina respectively. However, the maximum values of total Pb (127.53, 1084.96 and 106.99 mg.kg-1) were detected in Platycladus orientalis, Dodonaea viscosa and Myrtus communis respectively. The values of BF and translocation factor (TF) showed that Dodonaea viscosa is the most effective phytoremediator among the other studied plants.